Metode penulisan taqrib at-tahdzib karya Ibn Hajar - Amiruddin, Mochammad Adib (Maliki Interdisciplinary Journal, 2026)
This article discusses the method of writing the book Taqrib at-Tahdzib by Ibnu Hajar al-Asqalani, which is a summary and refinement of the book Tahdzib al-Kamal by al-Mizzi. The method of compiling this book focuses on easy access and clarity of information regarding hadith narrators, especially in the aspect of jarh wa ta'dil (criticism and assessment of the quality of narrators). Ibnu Hajar uses a systematic arrangement based on the alphabetical order of the narrator's names by abbreviating and cutting out information that is considered long-winded, as well as adding important information that supports the assessment of the narrator's credibility. In his preamble, Ibnu Hajar also determined the levels of jarh wa ta'dil which consisted of twelve levels and used special terms that had opposite meanings to avoid errors in assessment. With this approach, the book Taqrib at-Tahdzib becomes an important reference that makes it easier for students and scholars to study hadith sanads systematically and efficiently